Penerapan Model Pembelajaran Picture and Picture dalam Meningkatkan Keaktifan Belajar Sejarah Indonesia Siswa SMK Negeri 1 Tarakan pada Masa Pandemi Covid-19 - Andi Ibrahim (Al-Musannif, 2022)
Students’ interest in Indonesian history as one of the subjects in the national curriculum is still low and has implications for the lack of students’ active learning. This study aims to describe and analyze the implementation of the picture and picture learning model in increasing students’ active learning in Indonesian History subjects during the Covid-19 pandemic. This research is a classroom action research which consists of two cycles. The source of student activity data is Class X of Fashion Design at SMK Negeri 1 Tarakan, totaling 37 students. The source of data on the implementation of the learning process is the teacher (researcher). The success indicator is based on increasing students’ active learning by implementing the 7-step picture and picture learning model. The results showed that implementing the picture and picture learning model, could increase the students’ active learning of Indonesian history in class X of Fashion Design at SMK Negeri 1 Tarakan. This research has implications for the importance of active, innovative, creative, and fun principles in learning as an effort to stimulate students’ active learning in order to optimize learning outcomes.